Pengaruh Motivasi, Organisasi Pembelajaran Dan Budaya Organisasi Terhadap Berbagi Pengetahuan Pada Dinas LIngkungan Hidup Kota Yogyakarta - DWI ARDHIKA LAKSANA (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
This study aims to determine the effect of Motivation, Learning Organizations and Organizational Culture on Knowledge Sharing at the Yogyakarta City Environmental Office. This research method uses quantitative descriptive and primary data using a questionnaire. In sampling employees of the environmental service the sampling technique used is porposive sampling, one of the non-random sampling techniques where the researcher determines sampling by determining specific characteristics that are appropriate to the purpose of the study so that it is expected to answer the research problem. In this study the source of data to be used is the primary collected directly by researchers from respondents. Data obtained by distributing questionnaire questions containing questions on variables in the study. The number of questionnaires distributed was 40 questionnaires. Data were analyzed using multiple linear regression analysis. The results of this study indicate that motivation has a positive effect on knowledge sharing, whereas organizational learning and organizational culture have no effect on knowledge sharing. Keywords: Motivation, Learning Organization, Organization Culture, Sharing Knowledge